POLA KOMUNIKASI GURU PADA SISWA ANAK AUTIS DI SEKOLAH LUAR BIASA (SLB) MITRA ISWARA KABUPATEN TASIKMALAYA - Rostika Yuliani (Universitas Lambung Mangkurat, 2020)
The purpose of this research is to determine what factors affect the communication of teachers in students withautism extraordinary school of Mitra Iswara in the Tasikmalaya Regency. This research discusses howinstructional communication is carried out by teachers in students with autism. This research also answers whyschools choose to implement learning communication that combines autistic children students at the same timeand same class. The method used in this research is a qualitative method with a descriptive approach. Datacollection techniques used were non-participant observation and interviews. The results showed that the factorsthat influence communication between teachers and students with autistic children are teachers' competence. Inthis case, the ability to communicate in class both verbally or non-verbally. The second factor is how studentsare capturing lessons and material from the teacher. The third is the role of parents in the learning process,both at home and at school. The communication patterns that are implemented in Mitra Iswara usecommunication patterns in one direction..